Pendampingan Pembelajaran Mata Kuliah Psikologi Pendidikan pada Mahasiswa S1 Manajemen PAI - Firdausiyah, Jannatul; Zaini, Fina Magfirah; Helmi, Muhammad; Zakiyullah, Azkalakum; Amin, Moh Hasan Shodiqil; Habibah, Wulidatul; Muttaqien, Moh Hasan Firghol (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
This study aims to examine the influence of learning mentoring activities on improving the learning motivation of undergraduate students in the Educational Psychology course on the topic of Educational Motivation and Continuous Learning. The approach used is a descriptive qualitative approach using the Participatory Action Research (PAR) method, involving active interaction between undergraduate students in Islamic Religious Education Management and postgraduate students as learning mentors. Data were collected through observations, limited interviews, documentation, and simple questionnaires, then analyzed. The results indicate that an interactive, participatory, and collaborative learning approach involving mentors can increase student motivation, engagement, and reflective attitudes. These findings emphasize the importance of integrating collaborative learning strategies across levels in building continuous learning motivation in religious higher education.